Beethoven - Solomon, Maynard (New York Schirmer Books, 1998)
Product DescriptionHailed as a masterpiece for its original interpretations of Beethoven's life and music, this edition takes into account the latest information and literature. Includes a 30-page bibliographical essay, numerous illustrations, and a full-color pictorial biography of the composer.About the AuthorMaynard Solomon is a leading authority on Beethoven, winner of the Otto Kinkeldey Award for "Beethoven Essays" and the author of Mozart: A Life.